Condition assessment of marine structures using functional condition index approach - Ayop, Sallehuddin Syah; Mohamad Zin, Rosli; Ismail, Mohammad (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)

(untitled)
Marine structures are subjected to damage and deterioration during their service life because of continuous exposures to aggressive environment. As a result the performance and the intended functions of the structure are affected. This paper presents the development of a condition assessment system for assessing the status of concrete marine structures in Malaysia. The assessment system is based on the Condition Index (CI) method developed by the U.S Army Corps of Engineers. The assessment took into account the level of deterioration observed during inspection work. The Functional Condition Index (FCI) approach was used to calculate the CI of the structure. Field data through visual inspection on concrete wharf structure was collected. Three types of deterioration were considered in the assessment: (1) corrosion of reinforcement, (2) cracking, and (3) spalling of concrete surface. The results show that the calculated CI values based on the proposed method is relatively close to the expert opinion values. The condition assessment system based on the CI method is found to be reliable and efficient hence can be used to monitor the performance of marine structures in Malaysia.